(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Scale insects (Coccoidea) on fruit trees and non-crop plants growing near orchards were surveyed in the Aydin and Izmir provinces of Turkey during 1996-2000. The family best represented was the Diaspididae (18 species); most of these species were of economie importance in fruit-growing ecosystems. The Coccidae (7 species) were also well represented. Pseudococcidae (3 species), Margarodidae and Asterolecaniidae (2 species each), and Cerococcidae (1 species) also were collected. The distribution, frequency and economie importance of these species discussed.